2020
DOI: 10.1186/s12870-020-02534-w
|View full text |Cite
|
Sign up to set email alerts
|

TRANSTHYRETIN-LIKE and BYPASS1-LIKE co-regulate growth and cold tolerance in Arabidopsis

Abstract: Background: Cold stress inhibits normal physiological metabolism in plants, thereby seriously affecting plant development. Meanwhile, plants also actively adjust their metabolism and development to adapt to changing environments. Several cold tolerance regulators have been found to participate in the regulation of plant development. Previously, we reported that BYPASS1-LIKE (B1L), a DUF793 family protein, participates in the regulation of cold tolerance, at least partly through stabilizing C-REPEAT BINDING FAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…We previously demonstrated that B1L is involved in regulating freezing tolerance in plants (Chen et al, 2019(Chen et al, , 2020. However, other biological functions of B1L have remained unclear.…”
Section: Discussion Bypass1-like Is Involved In Lr Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that B1L is involved in regulating freezing tolerance in plants (Chen et al, 2019(Chen et al, , 2020. However, other biological functions of B1L have remained unclear.…”
Section: Discussion Bypass1-like Is Involved In Lr Initiationmentioning
confidence: 99%
“…We recently revealed that B1L interacts with 14‐3‐3λ to inhibit the degradation of C‐REPEAT BINDING FACTOR3 (CBF3) and positively regulates freezing tolerance in Arabidopsis (Chen et al, 2019). In addition, B1L interacts with TRANSTHYRETIN‐LIKE (TTL) to regulate growth and freezing tolerance (Chen et al, 2020). However, it is unclear whether B1L has other functions.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that B1L is involved in the regulation of freezing tolerance in plants (Chen et al, 2019; Chen et al, 2020); however, other biological functions of B1L remain unclear. In this study, we revealed a novel biological function and the elegant underlying molecular mechanism of B1L-mediated regulation of lateral root formation.…”
Section: Discussionmentioning
confidence: 99%
“…(Chen et al, 2019). In addition, B1L interacts with TRANSTHYRETIN-LIKE (TTL) to regulate growth and freezing tolerance (Chen et al, 2020). However, to the best of our knowledge, no study has been yet reported on the other molecular functions of B1L.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the TRANSTHYRETIN-LIKE (TTL) ttl-1 mutant promoted freezing tolerance. Therefore, B1L overexpression promoted plant freezing tolerance by interacting with TTL 19 . BR could also positively regulate the net photosynthetic rate and stomatal conductance under low-temperature treatment (8 °C), which promoted the growth and development of tung trees 20 .…”
Section: Introductionmentioning
confidence: 98%